Effect of electronic radiation on the evolution of nanostructure and creep of Zr at the temperature of 670 K - Karaseva, E.V.; Mats, A.V.; Mats, V.A.; Savchuk, E.S.; Sokolenko, V.I.; Тitоv, D.V. (Вопросы атомной науки и техники, 2020)
The effect of electron irradiation on the creep and evolution of the zirconium nanostructure obtained by the SPD method and previously relaxed by ultrasound is studied. It has been shown that the electron irradiation (with a dose of D = 5∙10¹⁹ cm⁻² and energy E = 10 МeV) does not change the character of the deformed zirconium nanostructure, but initiates the return processes at the grain boundaries and in the border areas, which leads to the softening of the material. The previously relaxation of internal stresses by ultrasound allows one to preserve a sufficiently high level of the strength and plasticity of nanostructured Zr after electron irradiation by reducing the intensity of dynamic recrystallization and activating an additional slip system in the creep process at 670 K. Виявлено вплив електронного опромінення на повзучість та еволюцію наноструктури цирконію, що отримана методом ІПД і попередньо релаксована ультразвуком. Показано, що опромінення електронами (дозою D = 5∙10¹⁹ см⁻² і енергією E = 10 МеВ) не змінює характер деформаційної наноструктури цирконію, але ініціює релаксаційні процеси на границях зерен і в приграничних областях, що призводить до знеміцнення матеріалу під час повзучості при 670 К. Попередня релаксація внутрішніх напруг ультразвуком дозволяє зберегти достатньо високий рівень міцності та пластичності наноструктурного Zr після електронного опромінення за рахунок зниження інтенсивності динамічної рекристалізації в процесі повзучості при 670 К Изучено влияние электронного облучения на ползучесть и эволюцию наноструктуры циркония, полученной методом ИПД и предварительно релаксированной ультразвуком. Показано, что облучение электронами (дозой D = 5∙10¹⁹ см⁻² и энергией E = 10 МэВ) не изменяет характер деформационной наноструктуры циркония, но инициирует возвратные процессы на границах зерен и в приграничных областях, что приводит к разупрочнению материала в процессе ползучести при 670 К. Предварительная релаксация внутренних напряжений ультразвуком позволяет сохранить достаточно высокий уровень прочности и пластичности наноструктурного Zr после электронного облучения за счет снижения интенсивности динамической рекристаллизации в процессе ползучести при 670 К.